(untitled) (Al-Qamar, 2023)
Atonement belief is the basic religious faith of Christianity .This faith is not found in The Bible .so this faith or belief is made by saint Paul .According to this faith all human being are born with original sin of Adam and eve . To save all human beings from original sin, ALLAH has sent his lonely son in the shape of man to scarify and to save humanity from hell .by believing this atonement Christian will not do good deed of shariah so they just believe on that Jesus who sacrificed himself and all of us are washed out from sins .and those who do not believe on the Jesus as savior will eventually go to the hell ,in view of all those belief of Christianity Islam has strong system of justice that no one cannot be punished by the sin of their ancestors, so Islam has strongly condemned all those false belief of Christian ,and gave them the right path to follow. In Islam prophet Jesus is believed as true prophet of Allah ,and He was born without father as a miracle .Christianity is now the world’s biggest religion made up of almost on the pillars of saint Paul.